Perlindungan Hukum Untuk Pernikahan Anak Menurut Undang-Undang Nomor 16 Tahun 2019 - Syaharani Putri Ubaidillah; Taun Taun (Peneliti.net, 2022)
This paper discusses the issue of legal protection for underage wedding in relation to Law No. 16 of 2019 amendments to Law No. 1 of 1974 concerning legal wedding by using a functional approach. Therefore, the nature of legal protection must be clarified first so that the concept of Legal Science can be interpreted correctly. Furthermore, this paper explains how the legal protection for underage children who marry early. The attitude of parents in responding to the pressures and demands of children when pressing for marriage at an early age, as much how to educate children to be able to think logically about their Marriage age is still not exact, the importance of the legal age of marriage, then the need for understanding.